The Possible Role of Transplacentally-Acquired Antibodies to Infectious Agents, With Molecular Mimicry to Nervous System Sialic Acid Epitopes, as Causes of Neuromental Disorders: Prevention and Vaccine Implications - André J. Nahmias; Susanne Beckman Nahmias; Dan Danielsson (Clinical and Developmental Immunology)
Proof of causality of most neuromental disorders (NMD's) is largely unavailable. Lessons from four-decade investigations of the epidemiology, immunology, pathogenesis, prevention and therapy of perinatal infectious agents, which invade directly the nervous system, have led us to propose a new indirect effect hypothesis: maternal transplacentally-acquired antibodies, to agents with epitope molecular mimicry with the developing nervous system, can cross the fetus/infant's blood–nervous system barriers to cause NMD's, clinically manifest years later.